All i-th Ramsey numbers for stars - Benedict, James M. (Utilitas Mathematica, 2005)
A formula is presented that computes, for each positive integer i, the i-th Ramsey number of any collection of stars. In particular for the positive integers i, k, and n1, n2, . . ., nk, it follows that ri(K(1,n1),K(1,n2),...,K(1,nk)) = [[1 +j=1ςk(nj - 1)] ÷ i] + θ where θ is either 0 or 1 and is completely determined as a function of n1, n2, . . ., nk, and i. Also, given any collection of stars, it follows that ri tends to 2 as i grows large. For such a collection, the least integer M is computed such that ri = 2 whenever i ≥ M.